Nexus between Green Finance, Creativity, Energy Accounting and Financial Performance: Banks Sustainability Analysis from Developing Country - Banani, Ade; Sunarko, Bambang (International Journal of Energy Economics and Policy, 2022)
Financial performance of financial institution especially banking sector is the essential element for economic growth and capture the attention of regulators and recent literature. Thus, this paper studies the effect of accessibility to green finance and conventional bank funding. Energy accounting and creativity on the banking sector’s fiscal performance of developing countries. For this purpose, data was collected from the financial statements of twenty central banks of developing countries from 2009 to 2020. Generalized method of moments and random model is used to test the study hypotheses. Obtained results indicated that green investment, green credit, energy accounting and creativity are positive correlated with the financial performance of the banking sector in developing countries. This study provides guidelines to the policy-making authorities while developing regulations related to financial performance, green finance availability, and creativity.